2019
DOI: 10.1021/acsami.9b03636
|View full text |Cite
|
Sign up to set email alerts
|

Bi2WO6 Semiconductor Nanoplates for Tumor Radiosensitization through High-Z Effects and Radiocatalysis

Abstract: The radioresistance of tumor cells is considered to be an Achilles' heel of cancer radiotherapy. Thus, an effective and biosafe radiosensitizer is highly desired but hitherto remains a big challenge. With the rapid progress of nanomedicine, multifunctional inorganic nanoradiosensitizers offer a new route to overcome the radioresistance and enhance the efficacy of radiotherapy. Herein, poly(vinylpyrrolidone) (PVP)-modified Bi 2 WO 6 nanoplates with good biocompatibility were synthesized through a simple hydroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…reported that poly(vinylpyrrolidone) (PVP)‐modified Bi 2 WO 6 nanoplates, which exhibits strong radiocatalytic activity for water splitting and ROS generation under X‐ray irradiation. [ 224 ] The results indicated that Bi 2 WO 6 nanoplates can effectively enhance radiotherapeutic efficacy. Similarly, in order to further enhance the catalytic activity of radiocatalysts, improving the utilization levels of X‐ray‐induced e − and h + is an essential strategy.…”
Section: Ros‐associated Nanomedicines For Disease Treatmentsmentioning
confidence: 99%
“…reported that poly(vinylpyrrolidone) (PVP)‐modified Bi 2 WO 6 nanoplates, which exhibits strong radiocatalytic activity for water splitting and ROS generation under X‐ray irradiation. [ 224 ] The results indicated that Bi 2 WO 6 nanoplates can effectively enhance radiotherapeutic efficacy. Similarly, in order to further enhance the catalytic activity of radiocatalysts, improving the utilization levels of X‐ray‐induced e − and h + is an essential strategy.…”
Section: Ros‐associated Nanomedicines For Disease Treatmentsmentioning
confidence: 99%
“…On this principle, Bi 2 WO 6 semiconductors were harnessed as both radiosensitizing nanoagents for enhancing the X‐ray energy deposition because of the presence of high‐ Z elements of Bi ( Z = 83) and W ( Z = 74) elements. [ 127 ] The semiconductor nature of Bi 2 WO 6 also enabled the radiocatalysis for the ROS production. The concurrent radiation energy deposition and radiocatalysis by Bi 2 WO 6 semiconductors achieved high and synergistic killing effect of cancer cells in vitro and desirable tumor‐suppressing outcome of tumor xenograft in vivo.…”
Section: Radiodynamic Therapymentioning
confidence: 99%
“…The same results have been reported for the in vivo safety of Bi-based NMs in previous studies. 3,4,29,61,62,74,75…”
Section: Hematology and Blood Biochemistrymentioning
confidence: 99%